Main characteristics of trade of the Hungarian cereals and oil crops between 2000 and 2010 and the effects of changes in intervention rules to the Hungarian cop sector from 2004 to 2010 - Fehér, István; Kiss, István (Applied Studies in Agribusiness and Commerce, 2013)
In this paper the trade of the Hungarian cereal and oil crops from 2000 and 2010 are introduced. The general attributes of the Hungarian crop sector are analyzed and a specific picture from aspect of the trade in Hungarian cereal and oilseed sector, with a focus on the quantity of the export and import of wheat, maize, rapeseed, sunflower and other crops and their main target countries. This article also aims to show the impacts of the changes in the EU’s intervention rules and provide analysis.